Pengembangan Strategi Bisnis Pada Desa Wisata Gamplong Kabupaten Sleman Sebagai Penggerak Agrowisata Berbasis Ekonomi Kreatif - Erni Dwi Puji Setyowati; Odi Andanu; Utari Yolla Sundari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This research presents SWOT analysis in Gamplong tourism village which has natural fiber craft agroindustry based on creative economy Sleman Regency. Internal and external conditions are needed to identify problems that occur to launch the best strategy in developing tourism villages. This reserach was conducted by doing an observation to figure out that tourism village based on creative economy has its own characteristics in developing the local potential especially in independent tourism villages because it can be role model for developing and growing tourism villages to develop their local potential. Conducting interviews to get internal and external factors of the tourism village The SWOT analysis is done by performing quantitative weighting and ranking against these factors by ten respondents from internal and external of tourism villages. The results of this research indicates that Gamplong Tourism Village is in cell V of Matrix IE where cell V presents growth and stability phase. The best strategy for this position is concentration through horizontal integration that is expanding the company how to develop business in other locations, and improve the types of products and services.